2020
DOI: 10.37737/ace.2.4_113
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain and Associated Occupational Factors among Nursery School Teachers: A Multicenter, Cross-sectional Study

Abstract: a BStra ct BacKgrOUnD Low back pain (LBP) is an important problem in occupational health, but little is known about LBP in nursery school teachers. MetHODS To determine the prevalence of LBP that needed medical treatment, LBP in their lifetime, factors associated with LBP, and work environment in nursery school teachers, we performed a cross-sectional study at Sakyo-ku in Kyoto City. We used multivariable logistic regression models to assess factors associated with LBP that needed medical treatment during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This cross-sectional study surveyed nursery school teachers from 21 nursery schools in Sakyo-ku Hoikushikai, a branch of Zenkoku Hoikushikai, which is the largest association of nursery school teachers in Japan to promote the welfare of children and their parents [ 8 ]. The recruiting process was described in the previous report [ 8 ]. We explained our survey in Sakyo-ku Hoikushikai, and 21 nursery schools out of 27 agreed to participate in the survey.…”
Section: Methodsmentioning
confidence: 99%
“…This cross-sectional study surveyed nursery school teachers from 21 nursery schools in Sakyo-ku Hoikushikai, a branch of Zenkoku Hoikushikai, which is the largest association of nursery school teachers in Japan to promote the welfare of children and their parents [ 8 ]. The recruiting process was described in the previous report [ 8 ]. We explained our survey in Sakyo-ku Hoikushikai, and 21 nursery schools out of 27 agreed to participate in the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-sectional studies have shown a high prevalence of LBP in nursery school workers [7][8][9][10][11][12][13][14]. In Japan, Tsuboi et al [7] and Kudo and Sasaki [8] reported point prevalence rates of 43.0% (n = 142) and 71.9% (n = 57; valid response rate: 63.2%; female: 100%), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, Tsuboi et al [7] and Kudo and Sasaki [8] reported point prevalence rates of 43.0% (n = 142) and 71.9% (n = 57; valid response rate: 63.2%; female: 100%), respectively. Yamamoto-Kataoka et al reported one-year and lifetime prevalence rates of 41.8% and 83.7%, respectively (n = 154; valid response rate: 38%; female: 93.5%) [9]. Isono et al revealed that the one-month and lifetime prevalence rates were 62.0% and 85.5%, respectively (n = 333; valid response rate: 56.9%; female: 100%) [10].…”
Section: Introductionmentioning
confidence: 99%
“…LBP is prevalent worldwide, causing a significant cost to the society (Katz, 2006;Morris et al, 2018). Workers engaged in manual material handling (MMH), lifting of heavy loads, such as nursing, construction, and mining, commonly experience LBP problems, and a reduction in the LBP risk caused by the MMH is expected (Josephson et al, 1998;Yamamoto-Kataoka et al, 2020;Adhikari et al, 2021;Gallagher and Mayton, 2007). As a solution, wearable assist apparatuses have been researched and developed (Toxiri et al, 2019(Toxiri et al, , 2017Miura et al, 2018;Lotz et al, 2009;Imamura et al, 2014;Kobayashi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%